INVESTIGATING THE EFFECTS OF USING THUTO LEARNING MANAGEMENT SYSTEM: A CASE OF THE NATIONAL UNIVERSITY OF LESOTHO - Sepiriti, Sepiriti (International Journal of Online and Distance Learning, 2021)
Purpose: This article aims at investigating the effects of solely using Thuto learning management system on NUL students while traditional interactions were temporarily postponed. Methodology: This study adopted a qualitative inquiry and the DeLone and McLean Model of Information Systems with the aim of gaining deeper understanding about the effects brought by the new way of learning at the university amid threats posts by the covid-19. Free attitude interviews were used to generate data from conveniently selected NUL students. Findings: The study revealed that though Thuto is ideal during this Covid-19 era because learning still happens, it has many challenges that needs to be addressed, they include the following; not being interactive, inaccessible and reduced students motivation. Unique Contribution to theory and practice: Given the challenges revealed, it is recommended that efforts have to be made to improve the efficiency and the reliability of Thuto learning management system and that, lecturers should use other online learning platforms that are more interactive. Keywords; Thuto learning management system, NUL, Students, Covid 19, Effects